Personal Qualities in the Structure of an Environmental Specialist’s Professional Competence - Oksana Tulska (Pedagogical Discourse, 2017)
The article analyzed the terms «professional competence» and «personal qualities» of a professional specialist and revealed the specificity of these concepts towards the future ecologists. Actuality of the personal traits formation of environmental experts that are associated with the specificity of their professional work and the environmental, economic and political situation prevailing today in our country. In this situation, the modern education should be focused on the development of the man’s personality, revealing his capabilities, talents and formation of identity, self-realization. The main result of the study should not only be the formation of the professional skills through mastery of relevant knowledge and skills, but also the formation of the personality.The activity of an environmentalist occurs in dynamic, often unpredictable situations. In such circumstances, the successful one can be only a specialist who is able to think independently and creatively, generate original ideas, immediately make innovative and yet optimal decisions. Besides, the professional work in the area of environmental protection is inherently socionomic, associated with the necessity to work in a team, establish communication connections with colleagues and representatives of other professional groups, scientists and the public, and therefore implies the need for the ability to choose the best ways to communicate in a situation of interaction, build appropriate professional relationships.The author proved that the personal qualities are of great importance in the structure of professional competence of environmental experts. An essential key to a perfect professional activity of an ecologist is the presence of such qualities such as dedication, perseverance, determination, initiative, independence, self-control; willingness to communicate with people, ability to negotiate, discuss and defend his own position; ability to prevent and constructively solve interpersonal contradictions and conflicts; fairness and responsibility; creativity; high level of formation of environmentally oriented values and environmental awareness.According to the results of the analysis of the philosophical, psychological and pedagogical literature, and peculiarities of the work of experts in environmental protection, the attention is focused on the importance of further developing of special techniques of the professional ecologists personal traits formation.Key words: competence approach, professional competence, personal qualities, professional orientation, educational process.